Changes in anemia and anthropometry during adolescence predict learning outcomes: Findings from a 3-year longitudinal study in India - Nguyen, Phuong Hong; Walia, Monika; Pant, Anjali; Menon, Purnima; Scott, Samuel P. (Elsevier, 2022)
Background: Anemia and poor physical growth during adolescence have far-ranging consequences, but limited longitudinal evidence exists on how changes in these factors relate to changes in learning skills as adolescents mature. Objectives: We examined the association between changes in anemia and physical growth during adolescence and learning outcomes. Methods: We used longitudinal data from the Understanding the Lives of Adolescents and Young Adults (UDAYA) project, which surveyed adolescents aged 10–19 years in northern India in 2015–16 and 2018–19 (n = 5963). We used multilevel mixed-effects logistic regression models to examine associations between changes in anemia/thinness/stunting status (four groups: never, improved, new, and persistent) and reading (ability to read a story) and math proficiency (ability to solve division problems) at follow-up. Results: Persistent anemia and stunting were higher among girls than boys (46% vs.8% and 37% vs. 14%, respectively), but persistent thinness was lower (7% vs. 16%). Improvement in anemia, thinness and stunting was 1.4–1.7 times higher among boys than girls. Boys who were anemic in both waves were 74% (adjusted odds ratio [AOR] 0.26, 95% confidence interval [CI)]: 0.12,0.59) and 65% (AOR 0.35, 95%CI: 0.16,0.76) less likely to be able to read a story and solve division problems, respectively, compared to boys who were non-anemic in both waves. Persistent thinness in boys was negatively associated with both reading (AOR 0.37, 95% CI: 0.21,0.66) and math proficiency (AOR 0.27, 95% CI: 0.16,0.46). Persistent stunting contributed to lower reading and math proficiency in boys and girls (AORs: 0.29 to 0.46). Boys whose anemia or thinness status improved and girls whose stunting status improved had similar learning skills at follow-up as those who were never anemic/thin/stunted. Conclusions: Persistent anemia, thinness and short stature during adolescence was associated with poor learning. Programs targeted at adolescents should contribute to nurturing environments that foster healthy growth and learning.